Alveolar Oral Layer Repair by Periosteal Grafts versus Maxillary Flaps and Gingivoperiosteoplasty: Techniques and Follow-up to Adolescence - Ahmed A. El Danaf, MD, PhD; Hatem H. Al-Ahmady, MDS, MD, PhD; Heba A. Eldanaf, MDS, PhD; Helmy A. Soliman, MD; Moustafa H. Elhelw, MD; Maurice F. Khalil, MD; Ibrahim A. Rizk, MD; Mohamed S. Donia, MD (Plastic and Reconstructive Surgery, Global Open, 2024)
Background:. Alveolar periosteoplasty during primary repair of cleft lip is still a topic of debate due to the fear exacerbating maxillary retrusion. The authors present their experience with early closure of alveolar clefts. The study aims to analyze gingivoperiosteoplasty (GPP) by comparing the use of locoregional flaps versus distant grafts for reconstruction of the lower layer of the primary palate cleft. Methods:. Seventeen infants underwent 22 alveolar cleft repairs. After nasal floor repair by nasal mucoperiosteum, the oral layer was repaired by maxillary or gingival periosteal flaps in seven patients with alveolar clefts less than or equal to 6 mm wide, and tibial or pericranial periosteal grafts in 10 patients with wider clefts. At teenage years, crossbites in three flap-GPP and three graft-GPP patients were compared with nine older adolescents without primary GPP. Results:. Alveolar clefts were perfectly sealed. Radiographs during the early 3 postoperative years showed new bone formation more posteriorly extended in patients who underwent graft-GPP. Teeth eruption and alveolar rigidity at the mixed dentition age eliminated the need for secondary bone grafting. The anterior crossbites in adolescent patients ranged between −2 and −14 mm; crossing was relatively smaller in patients with a younger age and without cleft palate. The mean crossbite was 7.2 mm in the six teenagers and 9.6 mm in the control cases. Conclusions:. Graft-GPP may be a good alternative to flap-GPP, particularly for wide alveolar cleft repair. Maxillary retrusion is aggravated in patients with cleft palate and older age at assessment. GPP may not increase crossbite.